Analisis Perilaku Masyarakat dalam Menghadapi Pandemi Virus Corona (Covid-19) - Nurika Khalila Daulay; Dwi Rahma Juli; Ferdy Ihza Mahendra; Sri Putri Anggraeini (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article aims to discuss people's behavior in dealing with the Corona virus (Covid-19) pandemic. Many people do not follow the government's advice to stay at home. The research method used in this study is a literature study with a descriptive analysis approach. The behavior of the community, especially in the Balai Jaya Kota sub-district, who does not care and does not listen to the appeal from the government will lead to an even greater spread of the Covid-19virus. Not only that, some of the village community are reluctant to accept masks from KKN students who are carrying out activities in Balai Jaya Village, Rokan Hilir District, Riau. The results of this study indicate that the behavior of the community in Balai Jaya Kota Village, Balai Jaya District, Rokan Hilir Regency, Riau still does not believe in the existence of the Covid-19virus and refuses to distribute masks.